The Perception Overview of Kindergarten and Elementary School Teachers on School Readiness - Susanti, Meria; Hidayati, Izzanil; Anggreiny, Nila; Maputra, Yantri (GoAcademica Research & Publishing, 2024)
School readiness is one of important factors that is needed to help children enter the elementary education. However, the characteristic needed in school readiness remains unclear. Most of the school usually has different consideration in differentiating student admission process. This study aims to determine the kindergarten and elementary school teacher perception of student readiness entering elementary school. Cross-sectional survey designed is used as research approach involving 195 kindergarten and elementary school teacher in 5 cities in West Sumatera. 5 open-ended question were given to 91 kindergarten teachers and 104 elementary school teachers. Content analysis was carried out to analyze the answer and group them according to the themes that emerged. In general, the result of this research found that kindergarten and elementary school teacher has similar perception of school readiness. Around 81% kindergarten teacher and 92% elementary school teacher said that school readiness is crucial for children entering elementary school. In detail, kindergarten and elementary school teacher think that age is the main consideration in student admission for elementary school. Other consideration is cognitive, social, and emotional ability.